Replication Data for "Measuring Consumption Over the Phone: Evidence From a Survey Experiment in Urban Ethiopia" - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
These files comprise dataset and do-files for reproducing results presented in the article, "Measuring Consumption Over the Phone: Evidence From a Survey Experiment in Urban Ethiopia" (Abate, de Brauw, Hirvonen, and Wolle, 2023). A detailed description of each variable in this dataset is included in section 4 of the article. The sampling procedure, data, and methods are described in section 2 of the article (https://doi.org/10.1016/j.jdeveco.2022.103026).